The Effectiveness of TBL for Enhancing Students´ Vocabulary in Ninth Grade Students at Centro Escolar Católico Madre del Salvador During Semester I, 2019 - Caballero Trujillo, Oscar Alfredo; Gonzales Navas, Tatiana Carolina (2024)
The fundamental purpose of this thesis work was to enhance ninth grade students’ communicative ability by the incorporation of the Theme-based Learning Approach (TBL). The research team through a previous observation identified the necessity of designing suitable activities for students’ improvement of their speaking skill. After stating clear objectives, researchers selected the appropriate tools and proposed an intervention plan to meet directly the students from Centro Escolar Católico Madre del Salvador response to TBL oral practices. Students had the main role in the class since they worked by themselves on information, reasoning, and personal opinion about the activities. Along with this, students’ oral performance was verified with their report at the end of every class. In consequence, this approach remains students’ constant use of the language in a real-life context. Learners were involved in the specific activities by integrating the new concepts, past vocabulary, and their own knowledge in their outcomes